2000
DOI: 10.1161/01.cir.102.11.1252
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 12-Lead T-Wave Morphology for Risk Stratification After Myocardial Infarction

Abstract: Computerized T-wave morphology analysis of the 12-lead resting ECG permits independent assessment of post-MI risk and an improved risk stratification when combined with other risk markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
180
6
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(207 citation statements)
references
References 46 publications
10
180
6
3
Order By: Relevance
“…Although many authors have repeatedly pointed out that ventricular gradient is an index of repolarization heterogeneity, only one prospective study has tested its prognostic value. 13 Our study confirmed the results reported by Zabel et al, 15 obtained with different dichotomy value (TCRT < 0.158). When we applied this cut-off value to our data, TCRT was again the strongest independent predictor of cardiac death (RR 4.5, 95% CI 1.3-15.3, p = 0.014), while the 657 Abbreviations as in Table II.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although many authors have repeatedly pointed out that ventricular gradient is an index of repolarization heterogeneity, only one prospective study has tested its prognostic value. 13 Our study confirmed the results reported by Zabel et al, 15 obtained with different dichotomy value (TCRT < 0.158). When we applied this cut-off value to our data, TCRT was again the strongest independent predictor of cardiac death (RR 4.5, 95% CI 1.3-15.3, p = 0.014), while the 657 Abbreviations as in Table II.…”
Section: Discussionsupporting
confidence: 91%
“…Despite these limitations it is reasonable to expect that TCRT would retain (at least partially) its prognostic power in patients post MI treated according to modern standards, as suggested by the study of Zabel et al 15 …”
Section: Limitationsmentioning
confidence: 99%
“…This index is not sensitive to subjective definition of the end of the T-wave and is therefore a reproducible and reliable index of cardiac repolarisation. This index was recently described to be a powerful predictor of mortality in various populations [12][13][14][15][16]. TCRT values tended to be more abnormal (smaller) in diabetic patients, even when glucose levels were normal and the abnormality became more marked during hypoglycaemia, suggesting that hypoglycaemia further increases the heterogeneity in global repolarisation.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, novel repolarisation analyses have been developed to evaluate the characteristics of cardiac repolarisation with greater accuracy. New descriptors of T-wave morphology and the spatial QRS-T angle have already been shown to have better prognostic values than QT interval or QT dispersion with regard to cardiac events in several populations [12][13][14][15][16] and increased complexity of ventricular repolarisation measured by principal component analysis of T-wave morphology has been found to distinguish patients with congenital long QT syndrome from unaffected participants [17,18]. Therefore, we decided to study the effects of controlled insulininduced hypoglycaemia on the T-wave loop and the QRS complex loop in type 1 diabetic patients and age-matched non-diabetic control participants.…”
Section: Introductionmentioning
confidence: 99%
“…ECG measures of the heterogeneity or complexity of ventricular repolarization have been implicated in the genesis of ventricular arrhythmias and also associated with adverse prognosis (6 -14). A number of surface ECG approaches to analysis of repolarization heterogeneity have been proposed, including QT dispersion (6,9,12), T-wave morphology analyses (9,10,13), and principal component analysis (PCA) of the T-wave vector loop (11,14), a spatial measure of T-wave complexity that avoids many of the theoretical and practical limitations of simple QT dispersion and improves prediction of CV death (11,14). However, these repolarization abnormalities may be strongly correlated with one another (11), and whether they provide independent prognostic information when examined together remains unclear.…”
mentioning
confidence: 99%